Birds - Maloney, Brenna (New York : Children's Press, an imprint of Scholastic Inc., 2023)
Full-color photos and short blocks of text entertain and explain the fastest and slowest birds in the animal kingdom.
Meet the birds -- #10 slowest bird: American woodcock -- American woodcock close-up -- #9: chicken -- #8: gentoo penguin -- #7: great horned owl -- #6: ostrich -- #5: Anna's hummingbird -- #4: grey-headed albatross -- #3: golden eagle -- #2: saker falcon -- #1 fastest bird: peregrine falcon -- Peregrine falcon close-up -- Birds fast and slow.
Includes index.
2.3
K-3
780L
Keywords: Birds -- Miscellanea -- Juvenile literature; Birds -- Locomotion -- Juvenile literature; Birds -- Miscellanea; Birds -- Locomotion; Birds